The effect of seaweed (Kappaphycus alvarezii) as a partial substitute for commercial feed on the growth of chicken. - Bedia, Alma Mae S.
The study determined whether the use of seaweed (Kappaphycus alvarezii) in different amounts as a partial substitute to commercial feeds would enhance the growth of chickens, rduce feed consumption, increase feed efficiency and increase profit. The chickens were first fed with commercial broiler starter mash feeds for 15 days. Then on the 16th day to 35th day, the chickens were fed with different combinations in 1;1, 1:2 and 1:3 ratios of commercial broiler finisher feeds of K. alvarezii. Chickens fed with purely commercial broiler finisher feeds served as the control. Feed consumption, liveweight gain and feed efficiency were computed every three days, while profitability was determined at the end of the experimental period., Results showed that the use of K. alvarezii as apartial substitute to commercial broiler finisher feeds in a 1:1 ratio increased the profit as well as the growth of the chickens, and it is comparable to that in the control (fed with purely commercial broiler finisher feeds). When the amount of K. alvarezii in the feed ration is more than 50 (1:1 ratio), it was observed that it would hamper the growth of the broilers.